Manajemen Strategi Bimbingan Manasik Haji dalam Meningkatkan Kualitas Ibadah Haji Jamaah - Pahmiyatul Ilmi, Diki; Sarbini, Ahmad; Rosyadi, Imron (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2015)
Guidance on Hajj rituals is an important part of organizing the pilgrimage as mandated by Law No. 8 of 2019 which aims to provide guidance, service and protection for pilgrims so that they can carry out their worship in accordance with the provisions of the Shari'a and realize the independence and resilience of pilgrims. Guidance on Hajj rituals is carried out by three institutions, namely Kemenag, KUA, and KBIH. The research method used is a comparative descriptive method with a qualitative approach. This study aims to determine the implementation of guidance on pilgrimage rituals at the Ministry of Religion, KUA, and KBIH in an effort to realize the independence of pilgrims. The results of the study show that from a comparison of the Hajj ritual guidance carried out by the Ministry of Religion, KUA, and KBIH it is known: First, the formulation of the strategy shows that the Ministry of Religion and KUA are government agencies while KBIH is the government's partner in guiding Hajj rituals, the challenge for the guidance of the Ministry of Religion and KUA comes from KBIH while KBIH challenges come from other KBIH. Second, the implementation of the strategy shows that the Ministry of Religion carries out guidance with a mass system while the KUA and KBIH use a group system, the Ministry of Religion and KUA are guided by the Kepdirjen PHU No 146 of 2022, KBIH is in accordance with the Kepdirjen PHU No D/799 of 2013, the cost of hajj guidance for the Ministry of Religion and KUA budget-based while KBIH is based on congregation costs. Third, the evaluation of the strategy shows that KBIH's guidance on Hajj rituals is seen as more important than government guidance, the guidance resource person lacks guidance techniques and the timing of implementation of the guidance from the Ministry of Religion and KUA is too close to departure, different from KBIH.